To increase trust in clinical research: Be worthy of trust and enhance the role of clinical research nurses - Rita K. Devine; Bernadette Capili; Rhonda G. Kost; James G. Krueger; Barry S. Coller (Journal of Clinical and Translational Science)
There has been an erosion of trust in medical care and clinical research, and this has raised issues about whether institutions and investigators conducting clinical research are worthy of trust. We review recent literature on research on trust and trustworthiness in the clinical research enterprise and identify opportunities to enhance trustworthiness, which will likely increase participant trust in clinical research. In addition, we review materials reporting the results of national polls related to the public’s trust in different occupations. The literature on trustworthiness and trust is complex and suffers from a lack of agreement on definitions of trust and trustworthiness and actions to enhance trustworthiness. Nonetheless, institutions need to take action to address the many elements that contribute to being perceived as trustworthy. As a complementary approach, since nurses have consistently ranked highest on trust by the public for twenty-two straight years, we analyze the features that likely account for the public’s uniform high regard for nurses. We propose specific actions to enhance the role of research nurses in the research enterprise, without compromising their primary role as participant advocates, that we have adopted at Rockefeller University to gain the benefits of the public’s trust in nurses in building trustworthiness.